GDF11 decreases bone mass by stimulating osteoclastogenesis and inhibiting osteoblast differentiation - Weiqing Liu (Nature Portfolio, 2016)
GDF11 is related to myostatin yet has no known role in postnatal bone turnover. Here the authors show that recombinant GDF11 injection causes bone loss and impairs healing by driving osteoclastogenesis while inhibiting osteoblast differentiation, plus they show that anti-GDF11 Ab can inhibit bone loss in ovariectomy and ageing mouse models.